Children in police custody: adversity and adversariality behind closed doors - Bevan, Miranda (Clarendon studies in criminology, 2024)
Drawing on the first comprehensive study in England and Wales to review the police custody process from the perspective of children, Bevan traces the child's journey from arrest, through detention and interview, to release or remand. A rights-based approach is used to evaluate the effectiveness of the protection under the present legal framework.